Valuasi Deplesi Sumberdaya Air dalam Rangka Penghitungan PDRB Semi Hijau di Kota Malang, Jawa Timur - Dian Hudawan Santoso; Farida Afriani Astuti (Jurnal Ilmiah Lingkungan Kebumian, 2019)
Green GRDP is a new index that is used to calculate the output of national and regional economies that take environmental factors into account. Semi-green GRDP is calculated only by considering the depletion factor of natural resources while Green GRDP considers depletion and degradation of natural resources in an area. Depletion of natural resources refers to the production, extraction, depletion, reduction in volume or amount of natural resources. This study aims to calculate the value of depletion of natural resources found in Malang, which is one of the major cities in East Java Province, so that in the end it can also be calculated Semi-Green GRDP which is part of calculating the value of Green GRDP. The method used is the method of surveying and observing, literature study, measurement and mathematical analysis. The results obtained are based on the identification of natural resources in the city of Malang, there is no volume extraction of natural resources found except on the use of water resources. Based on the data obtained almost all economic sectors utilize water resources for operational activities. Other objects that were assumed to be depleted were not found in the study area. Based on the analysis, it is known that the depletion value of using water resources absorbs around 0.354% of the total value of Malang City's conventional GRDP. Thus, the value of the Semi Green GRDP of Malang City by considering the depletion value of water resources decreased -0.354%. Keywords: Depletion; Malang City; Semi-Green GRDP; Water resources